Unlocking the gates to the peasants: are policies of ‘fairness’ or ‘inclusion’ more important for equity in higher education? - Pitman, Tim (Routledge, 2015)
Attempts to make higher education more equitable more readily succeed at the aggregate (sector) level than at the institutional, with students from disadvantaged groups being overrepresented in low-status institutions. It is suggested that this is because policies of ‘fairness’ (i.e. proportional representation) dominate the contemporary policy framework and are strongly resisted by elite universities. However, using the Australian higher education sector as an example, this paper argues that equity policy is actually a mix of ‘proportional fairness’ and ‘inclusion’ and elite institutions resist not because the policy is deficient but because it might actually work. An alternative approach to higher education equity policy is proposed; one which requires elite institutions to engage meaningfully with disadvantaged students but allows them to retain their status advantage.